The numerical model of the dynamics of asset prices - Valakevičius, Eimutis (Lietuvos matematikos rinkinys, 2023)
In the article is proposed the algorithm how to model the dynamics of asset prices by Markov process with continuous time and countable set of states.
Keywords: dynamics of asset prices; mixture of exponential distributions; Markov numerical model